Mistakes were made ebook A novel. - Wilsner, Meryl (St. Martin's Griffin, 2022)
"This blazing-hot forbidden romance manages to sensibly, and compassionately, capture the complexities of starting adult life after college and finding love and your identity in middle age. Cassie and Erin's romance is by turns delightfully raunchy and deeply emotional. This reader hopes Wilsner keeps these scorchers coming." - The Washington Post "[Wilsner writes] erotic yearning in a class all their own." - Entertainment Weekly From Meryl Wilsner, the acclaimed author of Something to Talk About, comes Mistakes Were Made , a sharp and sexy rom-com about a college senior who accidentally hooks up with her best friend's mom. When Cassie Klein goes to an off-campus bar to escape her school's Family Weekend, she isn't looking for a hookup—it just happens. Buying a drink for a stranger turns into what should be an uncomplicated, amazing one-night stand. But then the next morning rolls around and her friend drags her along to meet her mom—the hot, older woman Cassie slept with. Erin Bennett came to Family Weekend to get closer to her daughter, not have a one-night stand with a college senior. In her defense, she hadn't known Cassie was a student when they'd met. To make things worse, Erin's daughter brings Cassie to breakfast the next morning. And despite Erin's better judgement—how could sleeping with your daughter's friend be anything but bad?—she and Cassie get along in the day just as well as they did last night. What should have been a one-time fling quickly proves impossible to ignore, and soon Cassie and Erin are sneaking around. Worst of all, they start to realize they have something real. But is being honest about the love between them worth the cost? "Wilsner proves their serious romance range with a sophomore novel that laughs in the slow-burning face of their debut by kicking off with a hookup that'll have you fanning your face for days." - Buzzfeed "A steaming hot, thoughtful story about all kinds of love, featuring a firecracker of a couple that's impossible not to root for." - Women's Health